2022
DOI: 10.3390/agriculture13010054
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Protein Gel Treatments on Biometric and Biochemical Attributes of Tomato Seedlings in Greenhouse Condition

Abstract: Protein hydrolysates are widely used in agricultural crops for improving plant nutrient uptake, growth, yield, and fruit quality. Tomato (Lycopersicon esculentum Mill.) is one of the most important vegetables consumed around the world both for its good taste and rich content in vitamins, minerals, lycopene, and β-carotene. The objective of the present study was to assess the effect of new stimulant products based on protein hydrolysates obtained from animal tissue by-products on tomato seedlings. Given the inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Previous research conducted by Balan et al [18] on tomato seedlings showed that application of protein gels increased the content of assimilatory pigments (chlorophylls and carotenoids), sugars, and phenolic compounds in the leaves when compared to untreated plants. This research assumed that development of some vigorous seedlings would result in a higher production of tomatoes with improved nutritional qualities, so the present study aimed to evaluate the biocompound accumulation in the tomato fruit under biostimulant treatment.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Previous research conducted by Balan et al [18] on tomato seedlings showed that application of protein gels increased the content of assimilatory pigments (chlorophylls and carotenoids), sugars, and phenolic compounds in the leaves when compared to untreated plants. This research assumed that development of some vigorous seedlings would result in a higher production of tomatoes with improved nutritional qualities, so the present study aimed to evaluate the biocompound accumulation in the tomato fruit under biostimulant treatment.…”
Section: Introductionmentioning
confidence: 91%
“…The physicochemical characteristics of the protein gels were performed as previously described [18] and are presented in Table 1. The data are very similar, and differences in the bloom test and viscosity are due to the addition of keratin to the gelatin-based gel.…”
Section: Physicochemical Characteristics Of the Protein Gelsmentioning
confidence: 99%
“…Protein hydrolysates, especially those that contain antioxidant peptides, are obtained from natural components, and many researchers and scholars consider them biostimulants because of their minimum side effects, easy absorption, low cost, high activity, and lower molecular weight [ 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 ]. Protein hydrolysates and peptides can be used as notable ingredients in the formulation of functional foods [ 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 ]. They can be used as foliar sprays or through drip irrigation systems, and the amino acids can be absorbed through both leaves and roots [ 142 , 143 , 144 ].…”
Section: Protein Hydrolysatesmentioning
confidence: 99%
“…According to Golka et al [4], the use of biostimulators in the form of a gel helps to maintain the moisture of the plant by extensive water absorption, being mixed with the Gels 2024, 10, 75 2 of 16 soil, increasing the water capacity, counteracting water tensions by ensuring humidity for the plants, and reducing the evaporation of the water from the soil [5]. Another study [6] highlights the impact of the application of protein gels on tomato seedlings compared to samples of seedlings not treated with protein gels. After analyzing the leaves of tomato seedlings, it was found that the seedlings treated with the protein gels had a higher content of pigments, carotenoids, total phenolic compounds, and soluble sugars.…”
Section: Introductionmentioning
confidence: 99%